Non-aqueous, tissue compliant carbene-crosslinking bioadhesives - Shah, Ankur Harish (2020)
Surgical adhesives are an attractive alternative to traditional mechanical tissue fixation methods of sutures and staples. Ease of application, biocompatibility, enhanced functionality (drug delivery) are known advantages but weak adhesion strength in the wet environment and lack of tissue compliant behavior still pose a challenge. In order to address these issues, non-aqueous bioadhesive based on blends of polyamidoamine (PAMAM) dendrimer, conjugated with 4-[3-(trifluoromethyl)-3H-diazirin-3-yl] benzyl bromide (PAMAM-g-diazirine) and liquid polyethylene glycol (PEG 400) has been developed. PEG 400 biocompatible solvent reduces the viscosity of PAMAM-g-diazirine dendrimer without incorporating aqueous solvents or plasticizers, allowing application by syringe or spray. Upon UV activation, diazirine-generated reactive intermediates lead to intermolecular dendrimer crosslinking. The properties of the crosslinked matrix are tissue compliant, with anisotropic material properties dependent on the PEG 400 wt%, UV dose, pressure and uncured adhesive thickness. The hygroscopic PAMAM-g-diazirine/PEG 400 blend was hypothesized to absorb water at the tissue interface, leading to high interfacial adhesion, however porous matrices led to cohesive failure. The hydrophilic nature of the polyether backbone (PEG 400) shielded cationic PAMAM dendrimers with cured bioadhesive film displaying significantly less platelet activation than neat PAMAM-g-diazirine or PLGA thin films.